The Mediating Role of Work Motivation in the Relationship Between Compensation, Work Environment, and Employee Performance at Medistra Hospital - Agung Surya Dwianto; Lucia Rosdiana Damanik (Master of Management, School of Business and Management, Petra Christian University, 2024)
This study aims to explain the effect of compensation and work environment on employee performance with motivation as an intervening variable for nurses at Medistra Hospital. The type of research used in this study is a quantitative approach with the category of explanatory research. The population in this study were nurses at Medistra Hospital. The research sample was selected using the probability sampling method, namely 150 respondents. Data processing in this study was carried out using descriptive analysis and Structural Equation Modeling (SEM) analysis based on Partial Least Square (PLS). The results showed that in direct effect, compensation has an effect on employee performance, work motivation has no effect on employee performance, compensation has had an effect on work motivation, work environment has had an effect on work motivation. On the indirect effect, compensation has no effect on employee performance through work motivation. The work environment has no effect on employee performance through work motivation.